Virtual Screening of Drug-Like Compounds as Potential Inhibitors of the Dengue Virus NS5 Protein - García-Ariza, Leidy L.; Rocha-Roa, Cristian; Padilla-Sanabria, Leonardo; Castaño-Osorio, Jhon C. (Frontiers in Chemistry, 2022)
Dengue virus (DENV) is the causative agent of dengue fever. Annually, there are about 400 million new cases of dengue worldwide and, so far, there is no specific treatment against this disease. The NS5 protein is the largest and most conserved viral protein among flaviviruses and is considered a therapeutic target of great interest. This study aims to search drug-like compounds for possible inhibitors of the NS5 protein in the 4 serotypes of DENV. Using a virtual screening from a 642,759-compound database, we suggest 18 compounds with NS5 binding, and highlight the best compound per region, in the Methyltransferase and RNA-dependent RNA polymerase domains. These compounds interact mainly with the amino acids of the catalytic sites and/or that are involved in processes of protein activity. The identified compounds presented physicochemical and pharmacological properties of interest for their use as possible drugs; furthermore, we found that some of these compounds do not affect cell viability in Huh-7, therefore we suggest evaluating these compounds in vitro as candidates in future research.